Sejarah dan Akulturasi dalam Pedang Cikeruh - Tendi Tendi (Kemendikbud, 2020)
Cikeruh is a village located in Jatinangor, Sumedang Regency. In the colonial period, the village was famous as the production center of various kinds of weapons in the Priangan region. Consumers of the Cikeruh bladesmith varied, ranging from indigenous groups to Europeans groups in the Dutch East Indies. This article aims to reveal the history of Cikeruh’s bladesmith and explain the acculturation which is seen on the Cikeruh sword. The method used in this study is a historical method consisting of heuristics, criticism, interpretation, and historiography. Based on the study, it can be seen that the existence of Cikeruh bladesmith cannot be separated from the history of the Sumedang Larang Kingdom because the pioneer of Cikeruh bladesmith came from the royal descent of the kingdom. In addition, cultural acculturation can be witnessed from the Cikeruh blades that shows mixed models between Priangan and European styles.